2015
DOI: 10.15414/jmbfs.2015.4.4.369-372
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Yoghurts From Goat's Milk Enriched With Magnesium Chloride

Abstract: Goat’s milk can be enriched with magnesium in the form of chloride before pasteurization with a save dose, i.e. 20 mg of magnesium for 100 g of milk. Higher doses of magnesium can lead to coagulation of proteins since together with the increase of the dose of fortification there increases general acidity while pH of milk decreases. Together with the increase of the dose of fortification of yoghurts with magnesium there was shown an essential proportional increase of acidity and hardness of curds persisting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…They observed that, in milk fermented by S. thermophilus, when the concentration of Cu 2+ increased, the pH decrease was slowed down, which indicated that a higher concentration of Cu 2+ resulted in a longer fermentation time. Znamirowska et al (2015) also reported that goat's yogurts enriched with 5, 10, 15, 20 mg Mg 2+ 100 g -1 were characterized throughout 21 days of storage by higher pH values, compared to a control without added magnesium D-gluconate.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…They observed that, in milk fermented by S. thermophilus, when the concentration of Cu 2+ increased, the pH decrease was slowed down, which indicated that a higher concentration of Cu 2+ resulted in a longer fermentation time. Znamirowska et al (2015) also reported that goat's yogurts enriched with 5, 10, 15, 20 mg Mg 2+ 100 g -1 were characterized throughout 21 days of storage by higher pH values, compared to a control without added magnesium D-gluconate.…”
Section: Discussionmentioning
confidence: 90%
“…Münchbach and Gerstner (2010) reported that high levels of calcium, particularly insoluble forms such as carbonates and phosphates, tend to produce a chalky mouthfeel and may promote astringency or bitter taste in the finished product. The results of Znamirowska et al (2015) showed that fortification with magnesium gluconate decreases the sour taste of the yogurts in comparison to non-fortified ones. No significant differences were observed in the flavor scores of yogurts fortified with iron chloride, casein chelated iron, and whey protein chelated iron (Achanta et al, 2007).…”
Section: Microbiological Resultsmentioning
confidence: 98%
“…Znamirowska et al [ 37 ] determined a lower bacterial cell count (120,500 CFU mL −1 ) in goat milk. Another study reported TBC in goat milk of 359,000 CFU mL −1 [ 38 ]. Sikora and Kawęcka [ 39 ], investigated the suitability for cheese making using goat milk from the Saanen breed, and reported a total bacterial count of 100,000 CFU mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The ability of bisglycinate to neutralize milk could be used to increase enrichment doses with compounds that give milk an acidic character. Using the appropriate proportions between the alkaline-forming bisglycinate and calcium compounds that increase the acidity of milk may result in a desirable increase in the amount of the introduced mineral [ 4 , 38 ]. Moreover, the observation of cooled fortified milk samples carried out in this study did not show coagulation resulting in curdling of milk proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Znamirowska et al analysed the quality of raw goat's milk for the production of yoghurt [21]. The protein, fat and dry matter content were 2.69%, 2.98% and 10.78%, respectively.…”
Section: Resultsmentioning
confidence: 99%